2020
DOI: 10.1515/znc-2019-0163
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Dicaffeoyl-epi-quinic acid inhibits the PMA-stimulated activation and expression of MMP-9 but not MMP-2 via downregulation of MAPK pathway

Abstract: Matrix metalloproteinases (MMPs), especially MMP-2 and MMP-9, are very important gelatinases that are overexpressed during tumor metastasis. Up to date, several MMP inhibitors have been developed from natural sources as well as organic synthesis. In the present study, the MMP-2 and MMP-9 inhibitory effects of 3,5-dicaffeoyl-epi-quinic acid (DCEQA), a caffeoylquinic acid derivative isolated from Atriplex gmelinii, were investigated in phorbol 12-myristate 13-acetate (PMA)-treated human HT1080 fibrosarcoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Earlier, we had described that EMT is a factor that enhances the metastasis and migration of cancer cells. MMPs are also able to provide the metastasis and invasion of tumor cells via the degradation of the extracellular matrix (ECM) [125,126]. Among MMPs, MMP-2 and MMP-9 are important due to their ability in the degradation of major components of the ECM, including gelatin, collagen, and laminin [127].…”
Section: Relation Between Nob and Metastasismentioning
confidence: 99%
“…Earlier, we had described that EMT is a factor that enhances the metastasis and migration of cancer cells. MMPs are also able to provide the metastasis and invasion of tumor cells via the degradation of the extracellular matrix (ECM) [125,126]. Among MMPs, MMP-2 and MMP-9 are important due to their ability in the degradation of major components of the ECM, including gelatin, collagen, and laminin [127].…”
Section: Relation Between Nob and Metastasismentioning
confidence: 99%
“…MMP‐9 belongs to the extracellular protease family and plays a key role in airway remodeling, including extracellular matrix reorganization, regulation of protein degradation, and cell migration ( 25 , 26 ). The activation of MMP-9 is closely associated with the phosphorylation of MAPKs, which occurs in an asthmatic response ( 7 ). Lim and collaborators ( 27 ) reported that phosphorylation of MAPKs activated MMP-9 expression in OVA-challenged mice, and that MMP-9 levels were higher in samples from patients with allergic asthma, which were eliminated by MAPKs inhibitors ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, matrix metalloproteinase (MMP)-9 and mitogen-activated protein kinases (MAPKs) play a pivotal role in allergic asthma development (4,5). Previous studies have demonstrated that oxidative stress-driven MAPKs phosphorylation leads to the upregulation of MMP-9 expression, resulting in inflammation and airway remodeling both in vivo and in clinical trials (6)(7)(8). Therefore, inhibition of these signals may be an important therapeutic target for asthma.…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are generated by connective tissues and pro-inflammatory cells such as fibroblasts, osteoblasts, endothelial cells, macrophages, neutrophils, and lymphocytes under the control of various hormones, growth factors, and cytokines [16]. Their expression and activity can be regulated via multiple cellular signaling pathways, such as mitogenactivated protein kinases (MAPKs), and by various signal transduction pathways, such as p38 mitogen-activated protein kinase (p38 MAPK), c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinases (ERK), and nuclear factor-kappa B (NF-κB) [17,18]. MMPs are regulated at the gene transcription level, by post-translational modifications of the MMP protein, or by the endogenous or exogenous activation of enzyme precursors.…”
Section: Metalloproteinases (Mmps)mentioning
confidence: 99%